The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.sbspro.2015.01.892
|View full text |Cite
|
Sign up to set email alerts
|

Gamifying French Language Learning: A Case Study Examining a Quest-based, Augmented Reality Mobile Learning-tool

Abstract: Across the globe, over 3 billion hours a week are devoted to gaming, and with the ubiquitous presence of mobile technologies, gaming is now also mobile. A well-developed video game will keep a player enthralled for hours on end. What if educators could engage learners the way video games engage players? In fact, many educators are turning to gamification to do just that. Gamification uses game-based mechanics, and game thinking to engage people, motivate action, and promote learning. The principal goal of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
72
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(87 citation statements)
references
References 13 publications
3
72
0
4
Order By: Relevance
“…According to [1], -game-based feedback tools like experience points, progress bars, badges, and achievements are motivating and meaningful to students.‖ Games usually offer more consistent feedback, both immediate and delayed, than does the traditional learning. Research conducted by Haskell (as reported in [1]) at the university level indicates that gamification and quest-based learning have had positive impact on students' learning achievement.…”
Section: B Benefits Of (Web-based) Gamificationmentioning
confidence: 99%
See 2 more Smart Citations
“…According to [1], -game-based feedback tools like experience points, progress bars, badges, and achievements are motivating and meaningful to students.‖ Games usually offer more consistent feedback, both immediate and delayed, than does the traditional learning. Research conducted by Haskell (as reported in [1]) at the university level indicates that gamification and quest-based learning have had positive impact on students' learning achievement.…”
Section: B Benefits Of (Web-based) Gamificationmentioning
confidence: 99%
“…Research conducted by Haskell (as reported in [1]) at the university level indicates that gamification and quest-based learning have had positive impact on students' learning achievement. Those taking a quest-based course were reported to get higher grades compared to those who took a traditional course.…”
Section: B Benefits Of (Web-based) Gamificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have investigated the affordances of mobile gaming and have reported mixed results of specifically designed games on the participants' language learning, though they may promote more interaction [38]. Most studies report positive student feedback on mobile gaming [39,40]. Others have suggested that mobile games can be effectively combined with content-integrated language learning activities [41] and that place-based mobile games are a great opportunity to connect students with local contexts [42].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in [5] is presented an AR application used by VET students for basic mathematics skills, which is based on videogames. More studies, such as [6] present a Mobile Augmented Reality solution for learning French language which is based on gamification didactic method. The author, Bernadette Perry, describes gamification as "using gamebased mechanics, aesthetics and game thinking to engage people, motivate action, and promote learning" (p. 2309).…”
Section: Introductionmentioning
confidence: 99%